Pengembangan Corporate Identity dari PT. Telekomunikasi Indonesia sebagai Media Promosi untuk Publik - Tradiga Nur Aziz Aziz; R. Anang Muftiadi; Iwan Sukoco (Program Studi Manajemen FEBM UMRAH, 2022)
ABSTRACT : The logo is one of the media rather than the identity of the company, so the logo can be a feature to distinguish the characteristics of the company from one another. Corporate Identity is a sign of identity of the company as a differentiating medium with other companies. Corporate Identity design is able to represent the character and corporate identity which is applied in the form of logos, merchandise and other promotional media. PT. Telekomunikasi Indonesia is a company engaged in telecommunications. PT. Telekomunikasi Indonesia is tasked with serving all businesses in the telecommunications sector such as WIFI, telephone and internet services that will be used by customers. Targets from PT. Telekomunikasi Indonesia is all Indonesian people and companies that need fast internet service. There are shortcomings in the logo of PT. Telekomunikasi Indonesia in the form of images of waving hands and fists continued with the name Telekomunikasi Indonesia. Many take into account that the promotion for the logo of PT. Telecommunications Indonesia is still not exposed as a promotion, so that to overcome this, the author makes a Corporate Identity design for PT. Indonesian Telecommunications. This design procedure uses the Design Thinking method, this procedure carries out several stages, namely Emphatize, Define, Ideate, Prototype and Testing. The results of this design, in the form of a comparison of the old logo and the new logo for PT. Indonesian Telecommunications. The logo will be applied to several promotional media such as brochures, banners, and X-Banners. Keywords: Design Thinking, Promotional Media, Design, PT. Telekomunikasi Indonesia, Corporate Identity.